Technical Analysis and Liquidity Provision - Kavajecz, Kenneth A.; Odders-White, Elizabeth R. (Review of Financial Studies, 2004)
The apparent conflict between the level of resources dedicated to technical analysis by practitioners and academic theories of market efficiency is a long-standing puzzle. We explore a previously unexamined feature of technical analysis — namely its relation to liquidity provision. We demonstrate that support and resistance levels coincide with peaks in depth on the limit order book and moving average forecasts reveal information about the relative position of depth on the book. Furthermore, we show that these relationships stem from technical rules locating depth already in place on the limit order book.